The effects of privatization on exports and jobs - Yasuyuki Todo (IZA World of Labor, 2016)
The privatization of state-owned enterprises (SOE) in transition economies has often been found to improve employment and productivity of privatized SOEs, despite policymakers' fears regarding possible job cuts. This positive effect can be enhanced if privatization also promotes firms' exports. A recent firm-level analysis of China reveals that privatization has indeed a positive effect on export propensity, employment, and productivity in both the short and long term. The effect mostly stems from changes in firms' attitudes about profits and risks due to competitive pressure.
Keywords: F14; L32; P20; 330; privatization; exports; employment; state-owned enterprises; transition economies